Assessing the relationship between firm collaboration, trade publications, patent publications and firm innovation performance: Knowledge production function perspective - Emmanuel Arthur; Bernard Vanicek (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
This study draws on the axioms of the knowledge production function and open innovation to examine the influence of publications and firm collaborations on the innovation of micro and medium-sized firms in the EU. We utilized CIS 2018 data (Eurostat), employing logistic regression methods and doubly robust treatment estimation techniques for the analysis. Our findings indicate that trade and patent publications positively influence product and market innovation. Furthermore, we ascertained that micro- and medium-sized firms in the European region enhance their innovation performance when they engage in consultations with public and private research institutions and universities rather than purchasing licensing and IPRs from these institutions. We observed evidence suggesting that central government funding positively influences the impact of firm collaboration on market method innovation. We conclude by proposing practical implications for policymakers and managers of micro- and medium-sized firms across countries in the EU.
Keywords: O31; O32; O34; O36; O52; 330; Trade publications; Patent publications; Intellectual property rights; Innovations; Government funding